The complexity of Malay Muslim identity in Dina Zaman’s I am Muslim - Jerome, Collin (Penerbit UKM, 2013)
Malay identity has been an important area of research in the field of Malay studies. Many scholars have argued that Malay identity is a product of a complex interplay of various identity markers and a dynamic adoption of diverse identity strategies. While most studies have focussed on examining Malay language, culture and religion as dominant identity markers of Malays in Malaysia, there is still a need for more research on other identity markers in the production of Malay identity. This paper explores the complexity of Malay Muslim identity, particularly queer Malay Muslims who are featured in Dina Zaman‟s I am Muslim. Using the theories and research relating to ethnic, racial, and sexual identity, the paper analyses the markers and strategies employed by queer Malay Muslims in constructing their identities as well as the tensions and conflicts they experience in formulating a Malay Muslim identity marked by queerness. The results show that queer Malays in Dina‟s work adopt varied identity markers and strategies in formulating their own ethnic identity which include embracing both sexuality and religious faith. The results also show that the discord between religion and sexuality becomes a major obstacle to some queer Malays who wish to assert their self-identities, but are not able to do so because of their strong iman, taqwa and ahlaq. The paper hopes to contribute to the research on Malay identity by demonstrating that same-sex sexuality, in addition to normative markers of Malayness, play a pivotal role in identity creation among queer Malay Muslims.